2020
DOI: 10.1007/s00216-020-02525-8
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment-free analysis of anionic micropollutants in the sub-ppb range in drinking water by capillary electrophoresis-high resolution mass spectrometry

Abstract: Reversed-phase liquid chromatography (RPLC) used for water analysis is not ideal for the analysis of highly polar and ionic contaminants because of low retention. Capillary electrophoresis (CE), on the other hand, is perfectly suited for the separation of ionic compounds but rarely applied in environmental analysis due to the weak concentration sensitivity when coupled to mass spectrometry (MS). However, novel interface designs and MS technology strongly improve the sensitivity. Here, a method is presented ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Current analytical measurements for the most mobile substances are not widely available (the "analytical gap") and thus many go unnoticed and undetected in the water cycle ("the monitoring gap"). However, progress has been made to address this analytical gap and methods such as hydrophilic interaction liquid chromatography [23], supercritical fluid chromatography [24], mixed-mode liquid chromatography [25] and capillary electrophoresis [26] have now made it possible to analyse some of the most mobile substances. This progress also contributes to closing the monitoring gap as more of the most mobile substances can be detected.…”
Section: The Unknown Extent Of Pmt/vpvm Substances In Our Water Resoumentioning
confidence: 99%
“…Current analytical measurements for the most mobile substances are not widely available (the "analytical gap") and thus many go unnoticed and undetected in the water cycle ("the monitoring gap"). However, progress has been made to address this analytical gap and methods such as hydrophilic interaction liquid chromatography [23], supercritical fluid chromatography [24], mixed-mode liquid chromatography [25] and capillary electrophoresis [26] have now made it possible to analyse some of the most mobile substances. This progress also contributes to closing the monitoring gap as more of the most mobile substances can be detected.…”
Section: The Unknown Extent Of Pmt/vpvm Substances In Our Water Resoumentioning
confidence: 99%
“…In addition, the choice of the BGE is more limited as the requirements for MS compatibility are even higher than for sheath liquid interfaces. A compromise may be the sheath flow interface using electrokinetic pumping [102] or nanoESI [103]; however, its applicability to GLP still has to be shown. Comparing our method to LC-MS-based approaches, matrix effects were low despite the negligible sample preparation with degassing only.…”
Section: Discussionmentioning
confidence: 99%
“…The separation of the strong acids DFA and TFA was not sufficient. Just recently, Höcker et al [103] demonstrated the separation of strong acids (e.g., chlorinated and brominated acetic acids) using a new CE-nanoESI-MS method with LOQs below 0.5 μg/L. For a broad screening of strong organic acids, further BGE modifications may be necessary, adapting pH and possibly the addition of organic solvents.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] However, perfluorinated anionic surfactants possess strong adsorption properties that contribute to band broadening and/or poor resolution in CE when using aqueous BGE conditions with inadequate organic modifier content. 42 As a result, a nonaqueous BGE system was used for separation of PFASs in this work, which was composed of 70% v/v acetonitrile, 15% v/v methanol, and 5% v/v isopropanol;…”
Section: Methods Optimization For Pfas Analysis By Msi-nace-ms/msmentioning
confidence: 99%